Climatically Induced Degradation Processes in Conserved Archaeological Wood Studied by Time-lapse Photography. (17th February 2019) - Mortensen, Martin Nordvig; Chaumat, Gilles; Gambineri, Francesca; Kutzke, Hartmut; Łucejko, Jeannette Jacqueline; McQueen, Caitlin M. A.; Modugno, Francesca; Tamburini, Diego; Taube, Michelle
ABSTRACT: Samples of conserved archaeological wood of different ages, origins, and conservation histories were aged in a climate chamber for seven months, while the humidity alternated between 30% RH for 12 hours and 80% RH for 12 hours at a constant temperature of 30°C. Photographs were taken once every hour, which enabled the creation of a time-lapse movie. Some samples degraded visibly, whereas others were unaffected. Most of the samples were robust and would be able to survive well even in a very poor museum climate. Among the sensitive samples, three types of degradation were identified, namely disintegration, pyrite oxidation, and efflorescence of white crystals. Disintegration was ascribed to dimensional changes caused by the RH alternations in very fragile wood. The white efflorescence was interpreted as the recrystallization of an alum-associated substance, possibly mercallite (KHSO4 ). The pyrite oxidation was observed as the efflorescence of a thick yellow, grey, and green powder. Characterization of selected samples was performed using X-ray fluorescence spectrometry, X-ray diffraction spectrometry, scanning electron microscopy with energy dispersive X-ray spectroscopy, inductively coupled plasma – optical emission spectroscopy, Fourier transform infrared spectroscopy, ionic conductivity – liquid chromatography, and pyrolysis-gas chromatography-mass spectrometry with in situ silylation using hexamethyldisilazane.